Oxidation behavior of Ti–Cu binary metallic glass. (October 2015) - Park, Sung Hyun; Lim, Ka Ram; Na, Min Young; Kim, Kang Cheol; Kim, Won Tae; Kim, Do Hyang
Graphical abstract: Highlights: The oxidation behavior of Ti50 Cu50 metallic glass has been investigated. The oxide is in amorphous state below the glass transition temperature. With the increase of oxide thickness, crystallization of amorphous oxide occurs. Above T x, the Ti3 Cu3 O layer forms between two layers of TiCu4 and TiO2 . Abstract: The oxidation behavior of Ti50 Cu50 metallic glass has been investigated. When the oxide is in amorphous state blow the glass transition temperature, the diffusion rate of Ti ion from the matrix controls the growth rate of the oxide layer. With the increase of thickness, the amorphous oxide is crystallized into TiO2, which grows in inward direction by diffusion of oxygen ion through the oxide layer. Above the crystallization temperature, fast diffusion of Ti and oxygen ions through columnar grain boundary of TiO2 results in the formation of Ti3 Cu3 O underneath the oxide layer and TiO2 on the surface.